Determination of tipping points for aquatic plants and water quality parameters in fish pond systems: A multi-year approach. (May 2016) - Vanacker, Marie; Wezel, Alexander; Arthaud, Florent; Guérin, Mathieu; Robin, Joël
Highlights: Using a dataset of 100 fish ponds, we determined tipping points for aquatic plant richness and cover in fish ponds along a gradient of chlorophyll α, water transparency, Total N or Total P and over different years. We evaluated the relationship between tipping points, nutrient loads and weather conditions. The major tipping points ranged between 5 and 15 μg/L chlorophyll α concentrations. Tipping points can vary from year to year due to the influence of weather conditions on the competition between phytoplankton and aquatic plants. Abstract: High levels of nutrients in fish ponds by fish farming may cause significant eutrophication leading to a loss in species richness and a decrease of cover of aquatic plants to phytoplankton dominance. This shift can be represented by a tipping point where a significant change in the state of the ecosystem is observed such as a change from high to low aquatic plants species richness and cover. A total of 100 fish ponds were studied during five years in the Dombes region, France, to determine tipping points in aquatic plant richness and cover using chlorophyll α (CHL), water transparency, Total N (TN) and Total P (TP) gradients with two statistical methods. The relationships between tipping points, nutrient loads and yearly variations in weather conditions were also evaluated. Looking at the five years data, tipping points were observed in aquatic plant richness at 6 and 60 μg/L for CHL, and at 3.90 mg/L for TN concentration; as well as at 70 cm for water transparency, but no tipping point was found with TP. For aquatic plant cover, tipping points were observed at 11 μg/L for CHL, 2.42 mg/L for TN, 0.05 mg/L for TP, and at 62 cm for water transparency. These tipping points showed a significant decrease of aquatic plant species richness and cover, linked to the nutrient concentrations which drive the competition between the primary producers phytoplankton and aquatic plants. However, tipping points could vary significantly between years. The inter-annual variability may be due to an early occurrence of phytoplankton blooms in some ponds in a year preventing the establishment of aquatic plants, and thus influencing the value of tipping points. Weather conditions influence the competition between primary producers by impacting chlorophyll α and nutrients concentrations. When weather conditions supported increased nutrient concentrations, the development of phytoplankton and aquatic plants was facilitated and tipping points in aquatic plant richness and cover occurred with relatively high values. Thus, a significant decrease of plant cover and richness occurred at higher level of nutrients compared to the other years. In these cases, aquatic plants dominated over phytoplankton for the spring period, and also often during summer. In conclusion, tipping points observed are mainly linked to the competition between aquatic plants and phytoplankton. In shallow and eutrophic systems like fish ponds where nutrients are not a limiting resource, weather conditions act temporarily during spring as the main regulator of this competition.